Harrison & Market Streets, 1889. Johannesburg - Unknown (My University, 2011)
In the foreground is the old Standard Bank. In this photograph is embodied the character of the mining camp. A great forest of corrugated iron glistening in the midday sun.
Black and White Photograph.
Keywords: Harrison street, Market street, Johannesburg, 1889